Pengaruh Pendekatan Sistem Terhadap Motivasi Belajar Siswa di Sekolah Persatuan Amal Bakti - Maulidayani Maulidayani; Fatin Syahirah; Ibnu Qital; Nur Khotima; Salwa Putri Verhan (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to investigate the positive impact of using a systems approach on students' learning motivation at the Pesantren Amal Bakti School, with an emphasis on qualitative data. The research method used is a case study with a qualitative approach. Data was collected through in-depth interviews, observation and analysis of related documents. Data analysis was carried out by detailing qualitative findings that illustrate how the application of a systems approach contributes to increasing student learning motivation. The results of the research state that the systems approach significantly influences the increase in student learning motivation in the Unity Amal Bakti School environment. The implications of these findings can provide deeper guidance for increasing student learning motivation through systems approach strategies in the school context.